Impact of Mycotoxins on Aquaculture Fish Species: A Review. Issue 2 (25th September 2016) - Matejova, Iveta; Svobodova, Zdenka; Vakula, Josef; Mares, Jan; Modra, Helena
Abstract: As the use of ingredients of plant origin has increased in aquaculture, the potential for mycotoxin poisoning in fish has increased accordingly. Feeding fish with mycotoxin‐contaminated feed can lead to a breakdown in health, manifested as tissue damage or through immunosuppression. Both effects can lead to an increase in mortality. To date, however, there have been few reports of mycotoxins in feed at toxic concentrations. The aim of this study was to describe the effects of those toxic mycotoxins most commonly found as contaminants in fish feed. In terms of fish health, the most harmful mycotoxins are aflatoxin B1 and Fusarium mycotoxins. The most sensitive fish species was rainbow trout, Oncorhynchus mykiss . Future research in the field of mycotoxicosis in fish should be focused on the effects of combinations of mycotoxins.